FAKTOR FAKTOR YANG MEMPENGARUHI PENDAPATAN PETANI PINANG MENURUT EKONOMI ISLAM DESA SIMPANG DATUK KABUPATEN TANJUNG JABUNG TIMUR - Wahyu Fatahillah; Habriyanto Habriyanto; Agusriandi Agusriandi (Jurnal Kajian dan Penalaran Ilmu Manajemen, 2023)
Indonesia is a country that has extraordinary natural wealth because Indonesia is located in a tropical area which has high rainfall and sunlight almost all the time which makes plants grow fertile then has many mountains which are rich in minerals and has vast waters which are rich in minerals. marine animals and also Indonesia has abundant fertile land. Agriculture is the sector that receives the main attention in the development of food crop commodities. Indonesia is an agricultural country, where the main source of livelihood for the people is agriculture. This is motivated by geographical location. Indonesia is located in a tropical area, so the weather conditions, land and other resources in Indonesia have high potential to develop the agricultural sector. Based on these results, it can be concluded that all variables in this study are reliable. All variables have a normal distribution. This is proven by testing using the normality test. It is known that the Commodity Price, Land Area and Number of Areca Palm variables (X) and the farmer's income variable (Y) have values ​​greater than 0.05, so these variables have a significant effect. Based on the t test, the variables commodity prices, land area and number of areca nut have a significant effect on farmer income. The higher the price of commodities, the area of ​​land and the number of areca nuts owned and managed, the higher the price of commodities and the number of areca nuts and the area of ​​eating land that farmers' income will increase. Meanwhile, the analysis of commodity prices, land area and number of areca palms on farmer income based on test results (R2) has quite a large influence, namely 64.9%. Meanwhile, the remaining 35.1% was influenced by other factors not examined in this research. Thus, commodity prices, land area and number of areca nuts affect farmer income